Mechanical, thermal and morphological properties of durian skin fibre reinforced PLA biocomposites - Manshor, M. R.; Anuar, Hazleen; Mohd Nasir, Nur Aimi; Mohd Ithnin, Ahmad Fitrie; Wan Busu, Wan Nazri; Salit, Mohd Sapuan; El-Shekeil, Yousuf Ali Gumaan; Wahit, Mat Uzir (Elsevier, 2014)
Durian skin waste generated by durian fruit or Durio zibethinus Murray show potential as a new reinforcement based-natural fibre. Similar to other lignocellulosic fibre, durian skin fibre (DSF) is capable in reinforcing polylactic acid (PLA) through extrusion and injection moulding processes for various applications. In current study, the effects of fibre content and pre-treatment using 4% sodium hydroxide (NaOH) on DSF were investigated on impact and thermal properties of PLA biocomposites. Treated DSF significantly enhanced the properties of PLA biocomposites as compared to untreated biocomposite. PLA can be replaced by 30 wt% DSF for similar impact performance. Thermogravimetry analysis (TGA) demonstrated that pre-treated DSF improved the thermal stability of PLA biocomposite. Differential scanning calorimetry (DSC) showed the presence of pre-treated DSF minimally enhanced the glass transition temperature (Tg), crystallization temperature (Tc) and melting temperature (Tm) relative to untreated DSF which suggests on better reinforcement with NaOH pre-treatment.